First total synthesis of cyanobactins balgacyclamide A & B and synthetic efforts towards balgacyclamide C: configuration reassignment analyses via beta-hydroxyamides dehydrative cyclization conditions - Torres-Hernandez, Arnaldo Xavier (My University, 2025)
Balgacyclamides are a class of natural products, isolated from the freshwater cyanobacterium Microcystis aeruginosa, known for their potent antiparasitic activity against Plasmodium falciparum, Trypanosoma brucei rhodesiense, and Leishmania donovani. Previous studies have suggested that balgacyclamides may also exhibit metal chelation properties. Despite their promising biological activities, the total synthesis of these compounds has not been previously reported. This study presents the first total synthesis of the balgacyclamide family, providing insights into their stereochemistry, and exploring the potential for discovering new bioactive compounds through synthetic intermediates. Chemically, balgacyclamides A & B are macrocyclic hexapeptides that share a common northern fragment, which includes an oxazoline and a thiazole. However, their southern fragments differ; balgacyclamide A contains an additional oxazoline, while balgacyclamide B features a free [beta]-hydroxy amide. The total synthesis of balgacyclamide A, as well as its epimer, was achieved in 21 synthetic steps with overall yields of 5% and 3%, respectively. Key synthetic steps involved a tandem sulfur incorporation, cyclization, and radical oxidation to form the thiazole, along with a late-stage [beta]-hydroxyamide Walden inversion to access the two oxazoline rings. Notably, these oxazolines were derived from the cyclization of L-threonine and L-valine. Thus, we investigated the effect of [beta]-carbon epimerization at the threonine residue to determine the correct stereochemical assignment. Using reagents such as the Burgess reagent, diethylaminosulfur trifluoride (DAST), and (NH₄)₆Mo₇O₂₄·4H₂O catalyst, we compared our synthetic product with the configuration assigned to the isolated natural macrocycle and a previous synthetic study of balgacyclamide A. Our results led to a reassignment of the configuration from the prior reported synthetic route and confirmed a complete match between our synthetic balgacyclamide A and the isolated natural compound. In addition, balgacyclamide B was synthesized through a 17-step pathway with a 2% overall yield, following a similar balgacyclamide A synthetic strategy and employing standard peptide coupling conditions for macrolactamization. Finally, we explored the impact of molecular physicochemical properties on porin-mediated transport in Gram-negative bacteria (GNB) by synthesizing a library of northern fragment intermediates of balgacyclamides. We observed that altering the position of charged groups within the molecule, while maintaining other physicochemical properties constant, significantly affected penetration across GNB membranes. Notably, charge positioning influenced bacterial penetration, with transport rates ranging from 29% to 79%. This finding suggests that the three-dimensional orientation of charges plays a critical role in porin-mediated transport of small molecules in GNB. Future studies should focus on elucidating the mechanism behind charge orientation in porins and exploring the potential of balgacyclamides for drug delivery and metal chelation applications in greater detail.
Keywords: Balgacyclamide; β-hydroxyamide; Oxazoline; Cyanobactin; Cyclamide; Largazole